Metabolic Syndrome Needs Intervention - Helwick, Caroline (MD Conference Express, 2007)
This article describes the six risk conditions associated with the metabolic syndrome, and their appropriate interventions, including: abdominal obesity, atherogenic dyslipidemia, elevated blood pressure, insulin resistance/glucose intolerance, proinflammatory states, and prothrombotic states.